STUDY AND ANALYSIS OF ADDITIONAL DOPING OF NEODYMIUM RARE EARTH METAL ON MOS2 SEMICONDUCTOR - Muhammad Syahrul, Ridwan
Molybdenum Disulfide (MoSz) is a semiconductor material. MoS2 has many promising characteristics and one of them is its non-zero band gap compared to graphene. MoS2 acts as a semiconductor and due to its variable conductivity, MoS2 is efficient and effective for electronic and logic devices. With the promising prospect of MoSz, it means that the quality of MoS, properties can be increased higher for the needs of devices that require higher capacities and workloads. Therefore, MoSc is doped with Rare Earth Metals which have good electrical, optical, and physical properties and with the expaction of the properties of Mo$ 2 will also improve when doped. In this study, we will observe and analyze the impact of Neodymium Rare Eanh Metal doping on MoSc semiconductors. This material will be grown using an SiO2 sUbstrate and using DC Unbalanced Magnetron Sputtering for thin film growth of the material with a target MoSi:Nd of 7.5 at% with a total target mass of 5 grams. The grown thin films will later be characterized using XRD, SEM, EDX, UV-Vis, and I-V characterization to see the properties of MoS2:Nd 7.5 at% compared to pure MoS2. The growth of Nd doping on MoS2 was successful as indicated by the SEM and EDX results. In UV-Vis, the bandgap values of MoS2 and M 2:Nd were 2.607 eV and 2.532 eV, respectively, indicating a shift due to Nd doping. In the I-V characterization, there was an increase in the current density when the MoS2 thin films were doped with Nd. In the VSM characterization, an increase in the magnetic field occurs when MoSz is doped with Nd.